Fields virology. - Howley, Peter M.; Knipe, David M. (David Mahan), 1950-; Whelan, Sean P. J. (Wolters Kluwer Health, 2020)
Now in four convenient volumes, Field's Virology remains the most authoritative reference in this fast-changing field, providing definitive coverage of virology, including virus biology as well as replication and medical aspects of specific virus families. This volume of Field's Virology: Emerging Viruses, Seventh Edition covers recent changes in emerging viruses, providing new or extensively revised chapters that reflect these advances in this dynamic field. Bundled with the eBook, which will be updated regularly as new information about each virus is available, this text serves as the authoritative, up-to-date reference book for virologists, infectious disease specialists, microbiologists, and physicians, as well as medical students pursuing a career in infectious diseases. - Covers both basic science and medical features of each virus, emphasizing viruses of medical importance and interest, while also including other viruses in specific cases where more is known about their mechanisms of replication or pathogenesis. - Covers virus evolution, as well as Coronoviridae, Picornaviridae, Enteroviruses, Caliciviridae, Hepatitis C Virus, Filoviridae, Henipaviruses, Orthomyxoviruses, Bunyavirales, Arenaviridae, and much more. - Features over 500 full-color illustrations, including key figures for use as lecture slides. - Provides quick, flexible access to current information both in print and in an improved eBook format, searchable across all volumes. - Discusses virus structure, virus entry, replication, and assembly, virus-host cell interactions, host immune responses and vaccines, antiviral therapeutics, virus evolution and immunization.